Plasma Apolipoprotein-AIV Downregulated in Patients with Major Depressive Disorder having Suicidal Ideation Compared to those without Suicidal Ideation - Mathew, Boby; Srinivasan, Krishnamachari; Pradeep, Johnson; Thomas, Tinku; Mandal, Amit K. (Current Proteomics, 2022)
Background: Identification of a peripheral biological marker might aid in identifying patients at high risk of attempting suicide and might help in effective early intervention. Objective: In the present study, we extend the findings of our previous multidimensional proteomics study by examining the levels of plasma Apolipoprotein-AIV in patients diagnosed with major depression with and without suicidal ideation compared to age and gender-matched controls. Methods: Using the mass spectrometry platform, we quantified the levels of plasma Apolipoprotein- AIV in patients with major depressive disorder with and without suicidal ideation compared to matched controls with isotope-labelled peptides-based quantitative proteomics approach. Results: The targeted quantitative proteomics approach with isotope-labelled peptides showed that plasma Apolipoprotein-AIV was significantly downregulated in depressed patients having suicidal ideation 1.45 (CI:1.11-1.90) compared to those without suicidal ideation 0.88 (CI:0.77-1.003). Conclusion: These findings extend our earlier observation of downregulation of plasma Apolipoprotein- AIV in patients with suicidal attempts to depressed patients with suicidal ideation. The consistent downregulation of plasma Apolipoprotein-AIV observed in both the proteomics studies suggests Apolipoprotein-AIV might be a plasma-based biomarker for suicidal behaviour.
Keywords: biomarker